The possibility of optimization of the strength properties of the bars of the system Cold-box-amin - D. M. Kukuj; D. A. Kudin (Литьë и металлургия)
In the result of the multiple-factor experiment on the determination of strength characteristics of sticks of the system Cold-box-amin there is justified the possibility of reducing of negative influence of several factors of the process due to changing of the controlled parameters of the process.